PERANAN OPERASI PERDAMAIAN PERSERIKATAN BANGSA-BANGSA DI BURUNDI TAHUN 2004-2006 - Astitiningsih, Ni Komang; Priadarsini, Ni Wayan Rainy; Nugraha, A.A. Bagus Surya Widya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2015)
ABSTRACT This research aims to find the role of ONUB as a multidimensional peacekeeping operations in the post-conflict and multidimensional peacekeeping activities in Burundi, Africa in the period 2004 until 2006. ONUB established by United Nations Security Council in response to intrastate conflict in Burundi since the peace efforts undertaken by other parties have not been enough to create peace stability in Burundi . The method of research is descriptive-qualitative research. Technique of data collecting is library research. The results of this research showed that in the period 2004-2006 ONUB as a multidimensional peacekeeping operations have a significant role in in terms of maintaining long-term peace after conflicts in Burundi through elections, DDR and SSR programs despite the obstacles as attacks have been launched to their personnel while conducting the mandate . Keywords: ONUB, Burundi, Intrastate conflict, Multidimensional peacekeeping operations